Exploring the culinary tourism experience: an investigation of the supply sector for brewery and restaurant owners - Minihan, Christina, author; Donnelly, Maureen, advisor; O'Leary, Joseph, advisor; Kang, Soo, committee member; Bright, Alan, committee member (Colorado State University. Libraries, 2014)
Tourists travel all over the world to taste different types of cuisine and create memorable experiences through them. Although cuisine can be the primary reason one travels; it plays a significant role in any tourist's daily routine. While the idea of culinary tourism has been around for decades, it has received limited research attention. The existing research primarily highlights the consumer aspects, with limited focus on the trade or supply realm. The purpose of this dissertation is to present an innovative study in the culinary tourism field that develops and tests a comprehensive culinary tourism experience model from the supply sector perspective. This dissertation includes three studies presented as potential journal articles. Chapter 1 explores a review of the current literature on culinary tourism. This chapter contains the general frameworks and models that have been proposed to date when considering culinary tourism and the theory on experience. Chapters 2 and 3 include qualitative analyses that test a proposed culinary tourism experience model through in-depth interviews from breweries and restaurant owners in Fort Collins, Colorado. The model encompasses the following 14 components: (a) learning and knowledge, (b) physical setting, (c) quality, (d) quantity, (e) service quality, (f) variety, (g) backstage access, (h) local culture, (i) senses beyond taste, (j) entertainment, (k) sustainability, (l) target market, (m) differentiation, (n) social media, and technology. The elements were selected from the results that emerged from the literature review, along with a pre-test. These elements were examined with owners and managers in terms of how the restaurants and breweries manage their operation and create a customer experience. Implications for future research and recommendations for improving this supply side approach to modeling the cuisine tourism experience are proposed.
Keywords: brewery; culinary tourism; experience; owner / manager; restaurant; tourist